Impacts of FDI and Environmental Pollution in ASEAN Countries: The Role of Institutions - Nguyen, Yen; Le, Son; Ngo, Nam; Nguyen, Huyen (International Journal of Energy Economics and Policy, 2023)
The study aims to examine the role of institutions in the relationship between foreign direct investment and environmental pollution in ASEAN countries from 2000 to 2019. With the General Moment method, the results show that foreign direct investment impacts increasing environmental pollution. At the same time, aspects of institutional quality such as the rule of law, government efficiency, political stability, quality regulations, and voice and accountability reduce environmental pollution. Furthermore, the study shows that institutional quality is essential in reducing the negative impact of foreign capital inflows on environmental pollution in ASEAN countries. From these results, the study recommends that ASEAN countries implement environmental protection plans when attracting foreign investment flows.